2022
DOI: 10.3390/diagnostics13010080
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Bacterial Pathogens from Urinary Infections Associated with Struvite and Metabolic Stones

Abstract: Objective: The purposes of this multi-center study were to evaluate the rate of infection stones and to evaluate the urine cultures of patients with infection stones. Materials: Charts of adulpatients with urinary stones were reviewed and data on stone analyses and urine cultures were collected. Results: In total, 1204 renal stone formers (RSFs) from 10 countries were included (776 males, 428 females). Fifty-six patients (4.6%) had struvite stones. The highest frequency of struvite stones was observed in India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The high frequency of Staphylococcus spp. in our data is concurred with the study reported by [35] and [36], while our finding's contradicts with those of [37]. Moreover, this study showed that Staphylococcus aureus are the most common etiological agents causing UTIs in current study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The high frequency of Staphylococcus spp. in our data is concurred with the study reported by [35] and [36], while our finding's contradicts with those of [37]. Moreover, this study showed that Staphylococcus aureus are the most common etiological agents causing UTIs in current study.…”
Section: Discussionsupporting
confidence: 84%
“…One-hundred and fifty samples included of patients women and control group have been divided into four age groups in this study. The age group of females were (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), (25)(26)(27)(28)(29)(30)(31)(32)(33)(34), (35)(36)(37)(38)(39)(40)(41)(42)(43)(44), and (above 44 years). The study recorded the majority of both patients and control group were in the age (25-34) second group 46.3% and 38.10% respectively.…”
Section: A Sampling and Patient Demographicsmentioning
confidence: 99%
“…The re-emergence of the genus Pseudomonas in the struvite sample after its marked decrease in the stored urine can be explained based on a recent work on the bacterial pro le of kidney stones which revealed the presence of Pseudomonas in struvite stone (Halinski et al, 2023). The increase in abundance of Shewanella in the struvite sample can be attributed to the study by (Luo et al, 2018) which revealed the potential of Shewanella oneidensis strain as an inducer of struvite mineralization.…”
Section: Discussionmentioning
confidence: 93%
“…With the emergence of culture-independent approaches and the subsequent human microbiome project (Turnbaugh et al, 2007), studies revealed the presence of a unique microbiota in the urinary tract system (reviewed in Zuber et al, 2023), the microbial structure and composition is also reported to be subject to change with age, sex and health status (Halinski et al, 2023. Next-Generation Sequencing (NGS) targeting 16S rRNA was the most widely used approach to determine the bacterial portion of the urinary microbiome (Perez-Carrasco et al, 2021, Siddiqui et al, 2011, Lahr et al, 2016.…”
Section: Introductionmentioning
confidence: 99%